"Our Own Identity, Our Own Taonga, Our Own Self Coming Back": Indigenous Voices in New Zealand Record-Keeping - Wareham, Evelyn (Archivaria, 2001)
Indigenous people’s perspectives present strong challenges to records keepers in many parts of the world. In New Zealand, as in Canada, indigenous people have used the information held in archives to reassert their rights and reclaim the past. This article provides a case study of the rights and interests of New Zealand’s indigenous people, the Maori, in archives. Maori perspectives on archives are explored through first-hand accounts and analysis of developments in New Zealand archives, museum, and library environments towards the implementation of "biculturalism." It is argued that the Maori impact on record-keeping falls along a spectrum from reconnecting Maori with cultural information held in written records, to reclaiming control over management of these resources, to calling for records’ repatriation to their cultural owners.